Immunological Subsets Characterization in Newly Diagnosed Relapsing–Remitting Multiple Sclerosis - D’Amico, Emanuele; Zanghì, Aurora; Parrinello, Nunziatina Laura; Romano, Alessandra; Palumbo, Giuseppe Alberto; Chisari, Clara Grazia; Toscano, Simona; Raimondo, Francesco Di; Zappia, Mario; Patti, Francesco (Frontiers in Immunology, 2022)
Objectives Using flow cytometry, we characterized myeloid, B, and T cells in patients recently diagnosed with Relapsing Remitting Multiple Sclerosis (RRMS) naive to Disease-Modifying Therapies (DMTs). Methods This prospective-case-control study was conducted in the MS center, Catania, Italy. Demographic/clinical data and peripheral bloods were collected from 52 naive patients recently diagnosed with RRMS, and sex/age-matched healthy controls (HCs) in a 2:1 ratio. We performed flow cytometry on isolated peripheral blood mononuclear cells to assess immune cell subset differences between RMMS patients and HCs. We explored the biomarker potential of cell subsets using receiver operating characteristic (ROC) curves and relative area under the curve (AUC) analyses. Results Monocytic myeloid derived suppressor cells (Mo-MDSCs CD14+/HLADR-/low) and inflammatory monocytes (CD14+CD16+) displayed higher frequencies in RRMS patients when compared with HCs (p < .05). A lower percentage of B-unswitched memory cells was observed in RRMS patients when compared with HCs (p = .026). T-cells had a higher frequency of T-helper CD4+cells and their subset, CD4+CD161+ in RRMS patients when compared with HCs (p < .001). ROC analyses revealed an AUC > 70% for Mo-MDSCs CD14+/HLADR-/low and inflammatory CD14+CD16+, T-helper CD3+CD4+, and T-helper CD4+CD161+ monocytes. Conclusions Patients with a recent RRMS diagnosis and naive to DMTs showed peculiar myeloid, B, and T cell immunophenotypes.